The Impact of Taxes on the Reproduction of Natural Forest Resources in Ukraine - Жураківська, Ірина; Сидоренко, Роман; Фухело, Павліна; Хоменко, Людмила; Сокровольська, Наталія (INDEPENDENT JOURNAL OF MANAGEMENT & PRODUCTION(IJM&P), 2021)
The research was directed to confirming or disproving the hypothesis that increasing tax pressure on the forest industry encourages the irrational use of forest resources to cover tax payments. The purpose of the study is to develop a methodology for identifying the impact of taxes on the activities of forest enterprises in Ukraine, social and natural capital. In this study, we try to identify the causes of the increased tax burden and the impact of this process on forest conservation. The following decisions of the Government of Ukraine have been taken into account: ban on export of timber products in 2015; an increase in the rent for the use of forest resources in 2016; expiration of special VAT regime from January 1, 2017, introduction of land tax on forest lands from January 1, 2019, increase of deductions from net profit to the state budget from 75 to 90%. Information bases of research are the survey has been conducted, the statistic reporting, reporting to the State Forest Resources Agency and financial reporting of forestry enterprises. By means of methods of the econometric analysis, it is studied indicators relations of the amount of the paid taxes and the area of logging, the amount of the paid taxes and the area of restoration of the wood from 2010 to 2019. The impact of tax increases on the financial condition of forest enterprises was analyzed. The social effect was analyzed by studying the dynamics of payment of wage taxes, the environmental effect was analyzed by indicators of growth of areas of forest restoration including areas of planting a new forest. By results of the analysis of data of the State committee of statistics and the reporting of 17 state enterprises of the Volyn region which serve 7% of the total area of the woods of Ukraine it is established: tax revenues from forest enterprises have tripled, what is not related to the increase in profitability of their activities; reduction of the number of dividends paid in favor of the state; the total sectorial profitability of the activity decreased more than 6 times; bankruptcy is on the rise, and at the end of 2019 accounts for nearly half (65%) of all operating entities. The constructed econometric model allows us to claim with probability p = 0.95 that the increase in tax payments leads to an increase in the volume of harvesting although taxes should stimulate the economical use of forest resources. The results show that all government decisions as to increasing fiscal pressure on forestry enterprises were unsystematic and lead the industry into bankruptcy. This has a detrimental effect on the ecology of the region as forestry grows. However, instead of developing the industry, these studies indicate a complete decline as enterprises lack the resources to forestry development.
Keywords: Forest enterprises Taxes Tax burden Environmental taxation